Hukuman Tindakan Pidana Anak Terkait Perbuatan Pencurian Menurut Hukum Pidana Islam - Firmansyah, Muh. Fahmi (Islamic Criminal Law Study Program, Bunga Bangsa Cirebon Islamic University, 2021)
The purpose of this study is to show the view of Islamic law in criminal acts of children from the side of responsibility for criminal acts in terms of theft. This study uses normative juridical law research, by reviewing legislation, by looking at the normative aspect. The data used in this research is legal material. The results of this study indicate that the forms and criteria in Islamic criminal law that can be categorized as criminal acts of theft are in the form of behavior, unlawful nature, errors, constitutive consequences, accompanying conditions, additional requirements to be criminally prosecuted, and additional conditions to be convicted.